Transparent cap-assisted endoscopic sclerotherapy for esophageal variceal hemorrhage compared with conventional sclerotherapy: A retrospective case-control study - Wang, Zhiyong; Fu, Jinlong; Zhou, Gang; Wu, Jianliang; Sun, Liwei; Guo, Yun; Lai, Zhichao; Tang, Sensen (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Wang Z, Fu J, Zhou G, et al. Transparent cap-assisted endoscopic sclerotherapy for esophageal variceal hemorrhage compared with conventional sclerotherapy: a retrospective case-control study. Turk J Gastroenterol 2017; 28: 542-3.